Externality Analysis of Community Forest Management - Dahal, Mahesh Raj (The Third Pole: Journal of Geography Education, 2009)
This paper attempts to analyze the positive and negative externality effects of community forest management with the help of household level monetary value of benefits and costs derived from the sixteen community forest user groups of households in Arun River Valley. Monetary benefits of major types of forest products and total costs of forest use and management were calculated classifying into labour cost, transaction cost and membership fees to derive monetary estimation for the purpose of externality analysis. With the help of summary statistics of calculated gross benefits and costs including net benefits and the benefit-cost ratios (B/C) the externality effects of use and management of community forest were examined. The results of externality analysis shows that the poor income households are completely failed to internalize the benefit from CF as per the total gross cost per household incurred equivalent by negative net benefits (-4.0 percent). The middle income households are being able to internalize by equalize both of gross benefit (37.0 percent and the total gross cost (37.0 percent) from CF. The rich income households are being able to externalize the total gross cost on the poor income households to gain disproportionate net benefits (4.0) from CF. The benefit-cost ratios (B/C) for the poor (0.81 < 1), medium (1=1) and rich households (1.09 > 1) also have justified that the rich households are getting higher percentage of net benefits and paying less percentage of gross cost without providing any compensation to the poor households. The middle income households appeared in a position of no more gain nor more loss or zero net benefit. Since even a benefit loser, the poor households should take part in overall total gross cost of forest use, operation and management. Thus, the net externality effect of CF in terms of benefits accrued (positive externality) minus total gross cost incurred (negative externality) i.e. net benefit is negatively related to the poor income households and positively related to richer households in the study area. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1955 The Third Pole, Vol. 5-7, PP 62-69:2007